Educação, currículo e MST: o desafio de educar, conscientizar e organizar a luta. Um estudo de caso das Escolas de Assentamento Franco Montoro e Terezinha de Moura Rodrigues Gomes, Itapeva SP - Durval, Beatriz Araújo Lopes (2020)
The Landless Workers Movement has consolidated itself as one of the main references of the Latin American social movement. Part of this success was due to the ability to theoretically formulate their claims. One of them concerns access to public education for settlers (children, youth and adults). Inspired by the Education of the Countryside, the settlement schools became a space for experimentation of the so-called Pedagogy of the Movement. This concept, coined by the Movement, defends school as a space for articulation between knowledge and the struggle for Agrarian Reform. However, the introduction of these same schools in conventional public education created difficulties for the application of alternative pedagogical procedures. This research aims, through a case study of the Settlement Schools Franco Montoro and Terezinha de Moura, to analyze how this contradiction is structured. As research methodologies, we use participatory observation, conduct an interview and questionnaire, analyze the documents of the Schools and the Education Sector of the MST. For the debate on curriculum, we used the works of Bourdieu and Passeron (1982), Apple (1982,1989) , Goodson (1995) and Giroux (1981) as a theoretical framework